2016
DOI: 10.1016/j.jdent.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Dentist material selection for single-unit crowns: Findings from the National Dental Practice-Based Research Network

Abstract: Objectives Dentists enrolled in the National Dental Practice-Based Research Network completed a study questionnaire about techniques and materials used for single-unit crowns and an enrollment questionnaire about dentist/practice characteristics. The objectives were to quantify dentists’ material recommendations and test the hypothesis that dentist’s and practice’s characteristics are significantly associated with these recommendations. Methods Surveyed dentists responded to a contextual scenario asking what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
85
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 35 publications
1
85
0
9
Order By: Relevance
“…A 2016 survey reported that 32% of US dentists would choose full contour zirconia as the material of choice for a single unit posterior crown . Likely the use of zirconia crowns would have been less for those dentists who fabricated crowns with a chairside milling machine as there were few options for chairside fabrication of zirconia crowns until recently.…”
Section: Introductionmentioning
confidence: 99%
“…A 2016 survey reported that 32% of US dentists would choose full contour zirconia as the material of choice for a single unit posterior crown . Likely the use of zirconia crowns would have been less for those dentists who fabricated crowns with a chairside milling machine as there were few options for chairside fabrication of zirconia crowns until recently.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most appealing aspect of this new crown type is that it requires preparation specifications similar to those of cast metal. Despite the lack of existing clinical performance data and concerns regarding low-temperature degradation raised by some in the scientific community (Kelly and Denry 2008), many dentists have recommended and prescribed this new crown type for their patients (Makhija et al 2016) A recent systematic review comparing 5-y survival rates of single crowns suggests that several current all-ceramic crown types compare favorably to that of metal-ceramics when used on posterior teeth (Sailer et al 2015). Nearly all of the ceramic crown systems examined in this analysis were layered structures.…”
Section: Introductionmentioning
confidence: 99%
“…Practice busyness was also associated with the treatment planning process, as was the use of optical scanners . Clinician sex, region of practice, and hours worked per week impacted material choice for single‐unit crowns . Clinician race and ethnicity were associated with the likelihood that a clinician would accept an impression and send it to the laboratory for crown fabrication …”
mentioning
confidence: 99%